Olanzapine activates the rat locus coeruleus: in vivo electrophysiology and c-Fos immunoreactivity. - Dawe, G; Huff, K; Vandergriff, J; Sharp, T; O'Neill, M; Rasmussen, K (2001)
BACKGROUND: Activation of central noradrenergic pathways by atypical antipsychotics has been hypothesized to play a role in their efficacy in treating the negative symptoms and cognitive impairment of schizophrenia. Because acute administration of the atypical antipsychotic olanzapine has been shown to increase extracellular levels of norepinephrine in the medial prefrontal cortex, we examined the effects of olanzapine on the noradrenergic cells of the locus coeruleus (LC). METHODS: The effects of olanzapine (0.25-16 mg kg(-1), IV) on the firing rates and patterns of LC neurons were determined by extracellular, single-unit recordings in chloral hydrate-anaesthetized rats. The effects of olanzapine and clozapine on c-Fos expression in the LC, nucleus subcoeruleus part alpha (SubCA), and nucleus A5 (A5) were studied by immunohistochemistry. RESULTS: Olanzapine increased LC cell firing rates, de-regularized firing, and induced burst firing. Induction of c-Fos expression in the LC by olanzapine and clozapine was confirmed and was also found in the SubCA, but not in A5. CONCLUSIONS: Acute administration of olanzapine activates the noradrenergic neurons of the rat LC. This increased activity of LC neurons may play an important role in the efficacy of olanzapine and clozapine in treating both the negative symptoms and cognitive impairment observed in schizophrenic patients.